Evektivitas Pemerintahan Desa Puseurjaya Kabupaten Karawang Menuju Desa Mandiri - Alhevi Nuranggriani Maharani; Evi Priyanti; Eka Yulyana; Rudyk Nababan (Peneliti.net, 2022)
The goal of the village government in the administrative services arrangement has not been effectively marked by symptoms of dissatisfaction from the community service performed by the village government. Based on the phenomenon, research issues are formulated on the effectiveness of a village government organization to implement administrative services, with the aim of discovering factors that determine the effectiveness of a village government organization. As a whole the results of the study show that the organical services of village governments have not been fully implemented as yet can be seen from aspects of organizational authority and management and work programs as well as the management of vang problems to which they have not achieved a number of factors including leadership, authority, organizational structure, personnel, finance, tools and infrastructure, tatalaksana, and cultural organization as an intemal factor. As well as more extempore factors, his government policy, his coaching and monitoring, and his participation, as well as other extemporal factors